Power plant stability capacitors and grounding : numerical solutions - Acosta, Orlando N. (McGraw-Hill, 2012)
"Power Plant Stability, Capacitors, and Grounding is filled with numerical solutions of differential equations to help you solve complex electrical problems regarding the stability of power generating systems. After an overview of fundamental electrical engineering concepts, the book focuses on power system stability, high-voltage capacitors, safety, and electrical substation grounding systems. Case studies, problems, and examples are worked out and explained in great detail. The material presented in this practical guide is essential for the design, installation, operation, and maintenance of the vast network of interconnected electrical power systems"--Back cover.